IMPLEMENTATION OF CHARACTER EDUCATION VALUES IN ISLAMIC SCHOOL INTEGRATED TO IBNU ABBAS KEBUMEN - Indri Novianti; Lutfiana Rahmayanti; Rizki Isnaeni Putri; Siti Fatimah (Universitas Sebelas Maret, 2018)
This study aims to: a) find out the method of implementing the values of selected character education such as religious, honest, diligent, disciplined, and caring / responsible; b) knowing the religious behavior, honesty, diligence, discipline, and caring / responsibility of students in SDIT Ibn Abbas; and c) knowing the barriers to the application of character education values and solutions sought by the teacher. Research is a qualitative descriptive study by collecting data through interviews and questionnaires. The results of observation showed that the religious aspect was 54.73% with the category